Sylwa szlachecka jako archiwum pamięci i źródło wzorów stylistycznych - Szagun, Dorota (Stylistyka, 2019)
Noble sylva undoubtedly constitutes a special type of writing in the 17th and 18th centuries and is referred to by the researchers as the noble archive of memory. It preserves the most important traces that build the historical, state, family, cultural and literary (etc.) identityfor the community. At the same time, noble sylva, acting as a model, is for the then nobility a special erudite source of good style, understood as stabilised, conventional, and therefore typical and readable for the recipients of occasional literature.